Cinacalcet and primary hyperparathyroidism: systematic review and meta regression - Ng, Cheng Han (Endocr Connect, 2020)
PURPOSE: Primary hyperparathyroidism (PHPT) is a common condition affecting people of all ages and is mainly treated with parathyroidectomy. Cinacalcet has been widely used in secondary or tertiary hyperparathyroidism, but the use of cinacalcet in PHPT is less clear. METHODS: Searches were conducted in Medline and Embase for cinacalcet use in PHPT from induction to 10 April 2020. Articles and conferences abstracts describing the use of cinacalcet for PHPT in prospective or retrospective cohorts and randomized controlled trials restricted to English language only. We initially identified 1301 abstracts. Each article went extraction by two blinded authors on a structured proforma. Continuous outcomes were pooled with weight mean difference (WMD). Quality of included articles was assessed with Newcastle Ottwa Scale and Cochrane Risk of Bias 2.0. RESULTS: Twenty-eight articles were included. Normalization rate of serum Ca levels was reported at 90% (CI: 0.82 to 0.96). Serum levels of Ca and PTH levels were significantly reduced (Ca, WMD: 1.647, CI: −1.922 to −1.371; PTH, WMD: −31.218, CI: −41.671 to −20.765) and phosphate levels significantly increased (WMD: 0.498, CI: 0.400 to 0.596) after cinacalcet therapy. The higher the baseline Ca levels, the greater Ca reduction with cinacalcet treatment. Age and gender did not modify the effect of cinacalcet on serum Ca levels. CONCLUSION: The results from the meta-analysis support the use of cinacalcet as an alternative or bridging therapy to treat hypercalcemia in people with PHPT.